Brat Albert w eseistycznej wizji Marii Winkowskiej - Ołdakowska-Kuflowa, Mirosława (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
Maria Winowska (1904-1993), an émigré Polish writer, is the author of an essay biography of Adam Chmielowski – Brother Albert, entitled Frère Albert ou la Face aux outrages,published in 1953 in Paris and twice translated into Polish. It is, to date, the most exhaustive biography and, at the same time, a study of the spirituality of Saint Brother Albert, canonised in 1989. The present work points out certain similarities of Winowska’s essay and works of other writers who also charted the portrait of Brother Albert. The attention, however, is focused primarily on the peculiar features of the spiritual biography of the saint by Winowska, bringing to the fore the extraordinary figure of a man whose services to the Church and society, especially in alleviating poverty, cannot be overestimated.